It Wasn't Me! Visibility and Free Riding in Waste Sorting - Alessandro Bucciol; Natalia Montinari; Marco Piovesan (Lund University, School of Economics and Management, Department of Economics, 2014)
Free riding problems can be more severe in multiple-person social dilemmas than in two-person dilemmas, since agents can hide their actions behind the veil of anonymity. In this paper, we use field data on waste sorting to study the effect of visibility in social dilemmas. We compare the sorting behavior of households sharing (or not) their bin for unsorted waste. Since households have to pay a fee proportional to their unsorted waste production, sharing the bin means sharing the fee. We find that, on average, household unsorted waste production is higher if three or more households share the same bin. Surprisingly, when only two households share the same bin, and therefore the household sorting behavior can be identified, unsorted waste production decreases compared to users not sharing the bin. Our interpretation is that shame and fear of punishment may play a role between the two sharing users.
Keywords: D01; D78; Q53; 330; Social Dilemmas; Free Riding; Visibility; Waste Management